Oko duha - Vizjak-Pavšič, Mojca (Anthropos (Ljubljana), 1996)
While difficulties in studying mental imagery were in large part responsible for the Behaviorists' swing away from studying mental activity of any sort, the advent of computers has brought a new vocabulary for conceptualizing mental events. This new set of thinking constructs has allowed theories of mental imagery to be specified much more precisely than was heretofore possible. These clearer characterisations of the construct have, in turn, led to empirical studies that have revealed important properties about mental imagery and the imagery-processing system. With regard to their practical implications, mental images can be used to improve memory, in problem solving, and to improve creativity. Mental images can be used also to improve perceptual performance, modify visual-motor coordination, verify spatial relations among objects, compare rotated objects, and discover patterns made up of novel combinations of features. Future studies in mental imagery research will most likely focus on these and other practical uses of the perceptual properties of images.
Keywords: psihologija; psychology; mentalne predstave; spomin; memory; mišljenje